The Effectiveness of Mathematics Learning with Contextual Approaches for The Topic of Straight Line Equation in Junior High School - Lutfi, M K; Darwis, M; Syam, H; Prabawanto, S (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This research is experimental research involving two classes, namely experimental class and control class which was given different treatment. Purpose of this research is to know (1) the implementation of mathematics learning in grade VIII at Junior High School in Makassar taught with contextual approach, (2) the effectiveness of mathematics learning of students taught with contextual approach, (3) comparison of effectiveness between contextual approach and conventional approach in mathematics learning for VIII grade students at junior high school in Makassar for straight line equation topic. Subject of this research is students in grade VIII in one of junior high school in Makassar. The sample of this study was taken from two classes using cluster random sampling. Data in this research was collected by using written test (essay) for straight line equation topic. Data analysis technique used descriptive statistics and inferential statistics. The results obtained from the descriptive statistical analysis was as follows: (1) the implementation of learning with contextual approach was well implemented with average 3.86 (2) the application of contextual approach is effective in terms of aspects: (a) average of students’ post-test score taught with a contextual approach is 80.62, and students who completed minimum mastery criterion (KKM) is 76.92% ≥75% (fulfill classical completeness); (b) average of students’ learning activities is 3.53 (very good category); and (c) average of student responses to learning is 3.59 (positive categories). (3) the implementation of learning with conventional approach for topic of straight line equation was implemented well with average 3.83. (4) the application of the conventional approach in terms of aspects: (a) average of students’ post-test score taught with a conventional approach is 68.08, and students who completed minimum mastery criterion (KKM) is 52% ≤75% (do not fulfill classical completeness); (b) average of students’ learning activities is 3.47 (good category); and (c) average of student responses to learning is 3.4 (rather positive category). (5) Based on inferential statistical analysis, the result was obtained tcount> ttable (2.532 > 1.68) so that H0 was rejected. Therefore, it can be concluded that learning mathematics in the topic of straight line equation for VIII grade students in junior high school in Makassar taught with contextual approach is more effective than taught with conventional approach